From Interactions to Institutions: Microprocesses of Framing and Mechanisms for the Structuring of Institutional Fields - Gray, Barbara; Purdy, Jill M.; Ansari, Shahzad (Shaz) (Academy of Management Review, 2015)
Despite the centrality of meaning to institutionalization, little attention has been paid to how meanings evolve and amplify to become institutionalized cultural conventions. We develop an interactional framing perspective to explain the microprocesses and mechanisms by which this occurs. We identify three amplification processes and three ways frames stack up or laminate that become the building blocks for diffusion and institutionalization of meanings within organizations and fields. Although we focus on “bottom-up” dynamics, we argue that framing occurs in a politicized social context and is inherently bidirectional, in line with structuration, because microlevel interactions instantiate macrostructures. We consider how our approach complements other theories of meaning making, its utility for informing related theoretical streams, and its implications for organizing at the meso and macro levels.